Design method of material handling systems for lean automation—Integrating equipment for reducing wasted waiting time. Issue 1 (2017) - Yamazaki, Y.; Shigematsu, K.; Kato, S.; Kojima, F.; Onari, H.; Takata, S.
Abstract: The production systems of today are required to meet changing market conditions. To date, most conventional flexible systems depend on human flexibility. However, the demand for flexible automation systems is increasing owing to rising labor costs and quality requirements, even in emerging countries. To implement automation systems in the unpredictable market, cost reduction is essential to reduce the investment risk. However, there is no systematic design method for reducing the cost of automation systems. In this study, we propose a new design method wherein the waiting time of material handling equipment is reduced by allocating multiple operations to the equipment.